PENGARUH POLA ASUH ORANG TUA DALAM MENUMBUHKAN RASA KETAQWAAN PADA ANAK USIA DINI - Sri Wahyuni; Endah Wahyu Sugiharti (Al-ATHFAL: Jurnal Pendidikan Anak, 2026)
Parenting patterns are a primary factor in the character formation of early childhood, one of which is fostering a sense of piety towards God. This study aims to examine the influence of parenting patterns on fostering a sense of piety towards God in early childhood at TK Beringin Asri, Tegalombo District, Pacitan Regency. This study used qualitative methods. The results indicate that democratic parenting patterns tend to be more effective in instilling the value of piety than authoritarian or permissive parenting patterns. Piety in early childhood can be instilled through role models, habituating worship, memorizing short surahs, and good communication between parents and children. Therefore, the role of the family as the primary educator is crucial in shaping a child's religious character.